Effect of Four Dispersants on Biodegradation and Growth of Bacteria on Crude Oil - Mulkins-Phillips, G. J. (1974)
Four chemical dispersants, Corexit 8666, Gamlen Sea Clean, G. H. Woods Degreaser-Formula 11470, and Sugee 2 were examined singly and in individual combinations with Arabian Crude Oil (1:1 ratio) at 10 and 25 C for their effects on the growth of bacteria indigenous to local marine waters, the bacterial population composition, and biodegradation of crude oil; in addition, their emulsifying capacities, at approximately 24 C, were determined. None of the dispersants used alone were toxic even at relatively high concentrations (1.25%), although Gamlen Sea Clean and G. H. Woods Degreaser-Formula 11470 did cause an increase in the lag phase which was more pronounced at 10 than at 25 C; addition of the crude oil reduced the lag phase increase. All of the dispersants used alone supported good growth of microorganisms, but qualitative population shifts were caused by the dispersant-oil combinations. The degrees of degradation of the n-alkane fraction of the crude oil varied depending upon the dispersant used. Under these test conditions, only Sugee 2, which had the poorest emulsifying capacity, promoted n-alkane degradation compared with the values obtained by using the crude oil alone.